Characterization and phylogenetic analysis of the mitochondrial genome of Sarcocheilichthys sinensis (Bleeker) from Baima Hu Lake. Issue 1 (2nd January 2020) - Gong, Lurong; Lu, Yuexi; Gu, Lizhen; Dong, Lihui; Ren, Jiangfeng; Yang, Shoubao
Abstract: Sarcocheilichthys sinensis (Bleeker), is a small-sized benthopelagic fish with ornamental value. In the present study, the complete mitochondrial genome of S. sinensis was sequenced and determined. The complete mitogenome of S. sinensis was 16, 683 bp in length, consisting of 22 tRNA genes, 13 protein-coding genes, 2 rRNA genes, and 2 non-coding regions. The overall base composition of the S. sinensis mitogenome is 30.50% A, 26.28% T, 26.60% C, and 16.61% G, exhibiting obvious AT bias (56.79%). The phylogenetic analysis showed that S. sinensis clustered in genus Sarcocheilichthys . Present study provides useful data to population genetics and conservation biology of Sarcocheilichthys fishes.